Activity of Bacteriophage D29 Loaded on Nanoliposomes against Macrophages Infected with Mycobacterium tuberculosis - Silva, Ana P. B. [UNESP]; Roque-Borda, Cesar Augusto; Carnero Canales, Christian S. [UNESP]; Duran Gleriani Primo, Laura Maria [UNESP]; Silva, Isabel C.; Ribeiro, Camila M. [UNESP]; Chorilli, Marlus [UNESP]; da Silva, Patrícia Bento; Silva, Joás L.; Pavan, Fernando Rogério [UNESP] (MDPI, 2023)
The search for new antimicrobial agents is a continuous struggle, mainly because more and more cases of resistant strains are being reported. Mycobacterium tuberculosis (MTB) is the main microorganism responsible for millions of deaths worldwide. The development of new antimicrobial agents is generally aimed at finding strong interactions with one or more bacterial receptors. It has been proven that bacteriophages have the ability to adhere to specific and selective regions. However, their transport and administration must be carefully evaluated as an excess could prevent a positive response and the bacteriophages may be eliminated during their journey. With this in mind, the mycobacteriophage D29 was encapsulated in nanoliposomes, which made it possible to determine its antimicrobial activity during transport and its stability in the treatment of active and latent Mycobacterium tuberculosis. The antimicrobial activity, the cytotoxicity in macrophages and fibroblasts, as well as their infection and time–kill were evaluated. Phage nanoencapsulation showed efficient cell internalization to induce MTB clearance with values greater than 90%. Therefore, it was shown that nanotechnology is capable of assisting in the activity of degradation-sensitive compounds to achieve better therapy and evade the immune response against phages during treatment.
Keywords: intracellular activity; liposome; mycobacteriophage D29; Mycobacterium tuberculosis